Kebijakan dan Implementasi Manajemen Pendidikan Tinggi dalam Meningkatkan Mutu Pendidikan - Winarsih, Sri (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
In improving the quality of education, there should be sustainability of performance and quality improvement. The sustainable quality improvement serves as the measure to overcome the problems of low quality education which rely on conventional approaches. The quality assurance approach leads higher education institutions to learn and implement Total Quality Management (TQM). TQM is an integrated quality management undertaken by every level of managementand all units within the organizational system which aims at providing satisfactory service to the customer. So every Higher Education should optimize management to improve quality. There are four successful scopes of higher educationmanagement, such as: (1) students are satisfied with the higher education services; (2) educational customersare satisfied with the service to its students; (3) stake holders are satisfied to have graduates with high quality and meet theexpectation; (4) lecturers and staff are satisfied with the services of higher education in some areas: division of labor, relationships and communication between lecturers/leaders, employees, salary/honor received and service.ÙÙ ÙØ¬Ø§Ù ØªØ±ÙÙØ© Ø¬ÙØ¯Ø© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØªØ¹ÙÙÙ ÙÙØØªØ§Ø¬ Ø¥ÙÙ ØªØ±ÙÙØ© Ø±ÙØ Ø§ÙØ¹ÙÙ ÙØªØØ³ÙÙ Ø§ÙØ¬ÙØ¯Ø© Ø§ÙÙØ³ØªÙØ±. Ø¨ÙØ°Ø§ Ø§ÙØªØØ³ÙÙ Ø§ÙÙØ³ØªÙØ±Ù ÙÙØ±Ø¬Ù Ø£Ù ÙÙÙÙ ØÙØ§ ÙØ§ÙØ®ÙØ§Ø¶ Ø¬ÙØ¯Ø© Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙØªØ¹ÙÙÙ Ø§ÙØªÙ ÙØ§ ØªØ¹ØªÙØ¯ ÙÙØ· Ø¹ÙÙ Ø§ÙÙØ¯Ø®Ù Ø§ÙØªÙÙÙØ¯Ù.Â  ÙØ§ÙØªÙØ¬Ù Ø¥ÙÙ ØªØ±ÙÙØ© Ø§ÙØ¬ÙØ¯Ø© ØªÙØªØ¶Ù ÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ ÙØ¹Ø±ÙØ© ÙØªØ·Ø¨ÙÙ Total Quality Management (TQM). ÙØ°Ù Ø§ÙØ·Ø±ÙÙØ© ÙØ£Ø¯Ø§Ø© ÙÙØªÙØ³ÙÙ Ø§ÙÙØªØØ¯ ÙÙØ¬ÙØ¯Ø© Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ ÙÙ ÙØ±Ø¹ Ø¥Ø¯Ø§Ø±Ù ÙÙ Ø§ÙÙÙØ¸ÙÙØ© Ø¨ÙØ¯Ù ØªÙØ¯ÙÙÂ  Ø£ØØ³Ù Ø§ÙØ®Ø¯ÙØ§Øª ÙÙØ£Ø¹Ø¶Ø§Ø¡ ÙØ§ÙÙØ§Ø³. ÙØ°Ø§ ÙØ¥Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ ÙØ§Ø¨Ø¯ ÙÙ ØªÙØ¹ÙÙ Ø¬Ø§ÙØ¨ Ø§ÙØ¥Ø¯Ø§Ø±Ø© ÙØªØ±ÙÙØ© Ø§ÙØ¬ÙØ¯Ø©. ÙØ«ÙØ© Ø£ÙÙØ± Ø£Ø±Ø¨Ø¹Ø© ÙØªØ¹ÙÙ Ø¨ÙØ§ ÙØ¬Ø§Ø Ø§ÙØªÙØ³ÙÙ ÙÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ : 1)Â  ÙÙØ§Ø¹Ø© Ø·ÙØ§Ø¨ Ø§ÙØ¬Ø§ÙØ¹Ø© Ø¨ÙØ§ ÙØ¯ÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙØ 2) ÙÙØ§Ø¹Ø© Ø§ÙÙØ¬ØªÙØ¹ Ø¨ÙØ§ ÙØ¯ÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ ÙØ·ÙØ§Ø¨ÙØ 3) ÙÙØ§Ø¹Ø© Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØ³ØªÙØ¸ÙÙÙ ÙØ®Ø±ÙØ¬Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙØ 4) ÙÙØ§Ø¹Ø© Ø§ÙÙØØ§Ø¶Ø±ÙÙ ÙØ§ÙÙÙØ¸ÙÙÙÙ Ø¨ÙØ§ ÙØ¯ÙÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ ÙÙ ØµÙØ±Ø© ØªÙØ³ÙÙ Ø§ÙØ¹ÙÙØ ÙØ§ÙØªÙØ§ØµÙ ÙØ§ÙØªØ¹Ø§ÙÙ ÙÙÙØ§ Ø¨ÙÙ ÙÙØ³ÙØ¨Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙ ÙØ§ÙÙÙØ¸ÙÙÙÙØ ÙØ¬Ø§ÙØ¨ Ø§ÙØ±Ø§ØªØ¨ Ø§ÙØ´ÙØ±Ù ÙØ§ÙØ®Ø¯ÙØ§Øª.Â